Implementation of PowerPoint Media to Improve Language Learning Outcomes in Grade 5 in the Elementary School - Harlen Simanjuntak; Rolan Manurung (Institut Agama Islam Negeri Palopo, 2023)
Education is essentially an effort to pass on values, which will help and determine humanity in living life and at the same time improve the fate and civilization of mankind. Without education, it is believed that today's humans are not much different from past human generations, who, compared to today's humans, have been very left behind in terms of both the quality of life and the processes of empowerment. The success of learning is influenced by various things, one of the most important is the role of learning media. In situations like this, the teacher's ability as an important role holder is required to have imagination and a level of creativity that is above average in order to be able to deliver or deliver lessons as expected. This type of research is quantitative research. This research is referred to as a quantitative method because it contains numbers and also analyzes that use statistics in the process. This approach uses a quasi- experimental design approach, in which the researcher does not have full control over the external variables that affect the implementation of the experiment. This study uses a pretest-posttest group design, namely by comparing between before being given the imple-mentation of learning with PowerPoint media and afterwards. The conclusion from the research taken is that the use of PowerPoint media can improve learning outcomes in grade 5 of SD Negeri 066045 Medan in the 2022/2023 Academic Year.Â